A new WFD—compliant littoral macroinvertebrate index for monitoring and assessment of Mediterranean lakes (HeLLBI) - Mavromati, E.; Kemitzoglou, D.; Tsiaoussi, V. (2021)
Mavromati, E., Kemitzoglou, D., Tsiaoussi, V. et al. A new WFD—compliant littoral macroinvertebrate index for monitoring and assessment of Mediterranean lakes (HeLLBI). Environ Monit Assess 193, 745 (2021). https://doi.org/10.1007/s10661-021-09493-1